Meningkatkan Kemampuan Neurosains Melalui Spitirualitas Dalam Persepektif Pendidikan Islam - Pasiska, Pasiska; Mukmin, Taufik (Edification Journal : Pendidikan Agama Islam, 2025)
In this study, we will review improving the ability of Neuroscience through the perspective of spirituality of Islamic education, the method used in this study is qualitative research, namely research whose approach is library research library research research results of the research is that neuroscience is a science that studies human nerves, but most experts agree that the study discusses or focuses more on the brain. The purpose of this writing is to explain what Neuroscience itself is, how the history of Neuroscience is history, the function of Neuroscience, what is religion, what is spirituality and its differences, and the correlation of Neuroscience itself with spirituality, and the conclusion is that the more often a person does activities, the results obtained can make Neoscience itself healthier, because neuroscience is healthy, a person can carry out his activities to the maximum, especially when it comes to giving birth to creativity. In improving the ability of neuroscience from the perspective of Islamic education, namely by purifying one of them by performing ablution, according to some research results, by performing ablution can provide peace of mind, from a calm soul then make the mind positive and make oneself form good morals from these positive thoughts. In Islam, it is taught from the beginning of childhood and is able to form good character and morals.